2021
DOI: 10.14812/cuefd.955225
|View full text |Cite
|
Sign up to set email alerts
|

Investigating L2 Motivational Self System in the Turkish University Context

Abstract: This research explores how well L2 motivational self systems explain language learning motivation of university students in the Turkish context. To this end, data were collected from 668 university students in a state university in Turkey using a 51-item questionnaire and semi-structured interviews in this mixed methods research. The data from both the questionnaire and the interview indicate an overwhelming impact of language learning experience on the learners' motivation to learn English as a foreign langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Indeed, these external influences align with the domain of L2 learning experiences as per the L2MSS theory, which holds significant value for the surveyed students and wields substantial influence over their motivation for L2 learning. Although this study is primarily qualitative in nature, this result aligns with the findings presented by Taguchi et al (2009), Lamb (2012), De Burgh‐Hirabe (2019), You and Dörnyei (2014), and Course and Saka (2021). Lamb (2012) highlighted that the language teacher's role is potentially significant in translating generally positive attitudes toward English into actual learning endeavors, which aligns with the findings of this study, particularly regarding language teacher professionalism and the classroom ambiance set by teachers in relation to language learning.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, these external influences align with the domain of L2 learning experiences as per the L2MSS theory, which holds significant value for the surveyed students and wields substantial influence over their motivation for L2 learning. Although this study is primarily qualitative in nature, this result aligns with the findings presented by Taguchi et al (2009), Lamb (2012), De Burgh‐Hirabe (2019), You and Dörnyei (2014), and Course and Saka (2021). Lamb (2012) highlighted that the language teacher's role is potentially significant in translating generally positive attitudes toward English into actual learning endeavors, which aligns with the findings of this study, particularly regarding language teacher professionalism and the classroom ambiance set by teachers in relation to language learning.…”
Section: Discussionsupporting
confidence: 91%
“…Perhaps unsurprisingly they found that students with high ideal L2 self-scores tended to have more ‘promising and adaptive attributional styles’ (p. 350), in other words, they were more likely to attribute success to things more within their control rather than uncontrollable factors like ‘luck’ or ‘health.’ Drawing on similar principles to attribution theory, Demir-Ayaz and Erten (2021) surveyed university students to explore the effect of various factors – self-regulated strategy use, language learning effort, ideal L2 self, and imagination capacity – on their Directed Motivational Current. Similarly, focusing on university English as a foreign language (EFL) students’ L2 motivational self-systems, Course and Saka (2022) investigated the relative impact of language learning experience versus future images of their L2 selves on learners’ motivation to learn English. The past experience component was by far the strongest predictor of intended learning effort and thus motivation, both in terms of positive motivational impact, often attributed to particularly kind or effective teachers, and negative motivation (e.g., frustration over not seeing enough progress).…”
Section: Language Learning and Learnersmentioning
confidence: 99%